Analysis of the Relationship of Income with Household Food Security of Bajo Fishers During the Covid-19 Pandemic in the West Muna District - Selvi, Selvi; Limi, Muhammad Aswar; Zani, Munirwan (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This research aimed to look at the link between Bajo fishers' income and food security during the Covid-19 period in West Muna Regency. The study was carried out in Latawe Village, West Muna Regency. Because the community is a seaside village with many Bajo residents who primarily work as a fisherman, the study area was chosen with care. There were 64 families in this study's sample. The quantitative descriptive approaches were used to examine the data in this research. The illustrated method tries to assess the Bajo community's home food security. Measurement of income using income analysis and the share of food expenditure. The results of the study found that during the Covid-19 pandemic, there were fisherman Bajo who have more income small and more significant from MSE with category vulnerable food nor stand food and based on results analysis Chi-Square is known that there is the relationship between income with the household food security of Bajo fishers in West Muna Regency for the time of the Covid-19 pandemic. The expected role, as well as government, facilitate marketing results catch fisherman Bajo During Covid-19 pandemic period for guard income fisherman bajo following the MSE in force in the district West Muna